All Play and No Work: the Protestant Work Ethic and the Comic Plays of the Federal Theatre Project - (:unkn) unknown (My University, 2015)
Given the massive unemployment of the era, the subject of work dominated the politics and culture of the Great Depression. In particular, most government programs of the New Deal sought to provide jobs or reinforce long-standing American views of working. These aims were reflected by the Federal Theatre Project (FTP), which was charged with providing jobs to unemployed theatre workers and uplifting the spirits of audiences. But the FTP also strove to challenge its audiences by staging overtly political theatre. In this context, many comic plays -which have long been ignored by scholars of the FTP - actually challenged work norms of the 1930s. Backstage comedies, which focus on the lives of theatre workers, show characters who argue for the theatre - and by extension the FTP - to be more concerned with providing entertainment than making political statements. In hedonistic work comedies, the belief that work and pleasure could coexist for the middle class is disputed, while hedonistic work is promoted for laborers of the working class as a way to escape the rigors of work. In confidence artist plays, not only is swindling shown to be a form of work, but also that conning could serve as a model for workers to escape the rigors of what Max Weber called the iron cage of capitalism.
Keywords: Con Artist; Federal Theatre Project; Great Depressioin; New Deal; Theatre; Work